The empirical study of price differentials of air tickets between Dot Com and Dot Bam. - Ong, June Su Ling. (2008)
This project studies firstly, the price differentials of air tickets between the Dot Com and Dot BAM, secondly, the price dispersion of air tickets between the Dot Com and Dot BAM, and lastly, the frequency of price revisions of air tickets between the Dot Com and Dot BAM.